Training advice from pro triathlete Brad Kearns - Kearns, B.
Brad Kearns, former top professional triathlete and noted endurance coach offers tips on athletic training and leading a healthy lifestyle. This topic includes: - How to prevent overtraining and burnout - How to balance training and a busy lifestyle with the `Key Workouts Strategy` - Tips and techniques for successful racing (swimming tips) Author explains - what the Key Workouts Strategy is, how to schedule Key Workouts, - what the signs for overtraining are and how to mnitor the own body, which changes in training one can make in the case of overtraining - what the requirements for swimming are, how to build muscle strength for swimming, how to change ones attitude, some example workouts.